The effect of aqueous extracts of Nigella sativa on breast cancer cell line MCF-7: An in vitro study - Bumidin, Muhammad Solehuddin; Johari, Farah Azurin; Risan, Nurul Fikri; Mohd Nasir, Mohd Hamzah (Zibeline International Publisher, 2018)
Nigella sativa (NS) or also known as black seeds is one of the traditional herbs that were identified to have anticancer properties due to the presence of an active compound, thymoquinone. In this study, the cytotoxic effect of the aqueous extracts of NS were tested on the breast cancer cell line, MCF-7. Aqueous extraction of NS using cold water producing 3.8% of yield. The cytotoxic effect of aqueous extracts of NS were tested after incubation at 5 hours, 24 hours and 48 hours by using a modified MTT colorimetric assay. Interestingly, the IC50 of aqueous extracts of NS on MCF-7 was at 11.5 µg/ml. Additionally, aqueous extracts of NS at the concentration beyond 11.5 µg/ml causing the swelling of MCF-7 and leads to cell burst. In conclusion, aqueous extracts of NS have been proved to have cytotoxic effect on MCF-7.